On a family of (1,7)-polarised abelian surfaces - Marini, Alfio (MATHEMATICA SCANDINAVICA, 2004)
We study the geometry of the moduli space of $(1,7)$-polarised abelian surfaces with canonical level structure in detail. In particular we describe the locus where the syzygies of the embedded Heisenberg-invariant abelian surface degenerate, and relate this to the other known descriptions of the moduli space in question.